(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
he study examined debt recovery strategies of Commercial banks in First Bank of Nigeria Plc. Data were drawn from a sample size of 109 staff of First Bank Nigeria Plc., Calabar, Cross River State, using purposive sampling technique. Sample percentage and frequency distribution was used for demographic data analysis. Survey research design was used as well assimple linearregression. The findings revealed that; there was significant positive effect of guarantors on return on assets. Collateral and litigation also have a significant positive effect on return on assets. Based on the findings it was recommended that commercial banks should ensure that owners of collateral pay their loans on time to ensure returns on assets. Moreover, the commercial banks should strengthen the use of guarantors to reduce the burden of bad debts and risks.